The Effect of Effective Communication with Situation Background Techniques, Assessment, Recommendations on Patient Safety at Bhayangkara Hospital 2024 - Asia, Sri; Majid, Ruslan; Yuniar, Nani (Journal of Health Science and Medical Therapy, 2024)
Effective communication is an important element in professional nursing practice and a major element of patient safety goals because communication is the first cause of patient safety issues. The purpose of this study is to examine effective communication based on situation techniques, background techniques, assessment techniques and recommendation techniques for patient safety at Bhayangkara Kendari Hospital. Type of research with a cross-sectional approach. Data analysis was performed with SPSS statistical tests using univariate, bivariate and multivariate analysis. The sample in this study was 93 people, the sampling technique is a total sampling method.The results of this study showed that the situation technique had an insignificant influence on patient safety at Bhayangkara Kendari hospital with p values of 0.710 > 0.05. The background technique has an insignificant influence on patient safety at Bhayangkara Kendari hospital with p values of 0.234 > 0.05. The assessment technique has a significant influence on patient safety at Bhayangkara Kendari Hospital with p values of 0.003 < 0.05. The recommendation technique has a significant influence on patient safety at Bhayangkara Kendari hospital with p values of 0.031 < 0.05. For the nursing profession, the results of this research can improve the quality of service by sharing experiences. Future research will need to explore other factors that affect patient safety, such as infection prevention and fall risk, to support improved hospital care practices.